Pengembangan media pembelajaran berbasis website pada materi bangun ruang sisi datar di SMP - Dian Eka Khusnul Khotimah; Slamet Riyadi; Tatik Retno Murniasih (Math Didactic: Jurnal Pendidikan Matematika, 2017)
The purpose of this study is to describe the steps of learning media development and design of web-based learning media content with Adobe Dreamweaver CS5 on the building flat side room easy to understand for students as well as test the feasibility of media-based learning website so worthy of use as teaching materials and media self-learning for student. In this research use development method with model used ADDIE model (Analysis, Design, Development, Implementation, Evaluation).Validation trials conducted in this study are validation testing on media experts, validation test on the material experts, as well as trials on students of class VIII B which amounted to 37 students. Based on the results of validation of learning media based on this website, among others, the results of validation testing on media experts with a percentage of 85.83%. Result of validation experiment on material expert with percentage equal to 83.70%. And the results of the test on the students get a percentage of 76.72%. And the average yield percentage of the three test cobatersebut of 82.08%. So from the average result of validation percentage obtained that this web-based learning media declared valid and decent for use in learning.